Graphene on clean (0001) α‐quartz: Numerical determination of a minimum energy path from metal to semiconductor. Issue 9 (18th May 2016) - Colle, R.; Menichetti, G.; Grosso, G.
Abstract: By means of DFT calculations, we have individuated a minimum‐energy path connecting two energy minima of clean graphene on clean and relaxed oxygen‐terminated (0001)'SiO 2 substrate in the α ‐quartz configuration: one characterized by mutual graphene–SiO 2 substrate distance of ∼ 2.8 Å and weak (van der Waals) bonds between them, the other by mutual distance of ∼ 1.4 Å, and presence of strong covalent C–O bonds. Our calculations show that the pathway connecting the two minima goes through a transition state and that the two minima are separated by a barrier of ∼ 2.25 eV. The covalent C–O bonds, which characterize the lower‐energy configuration, induce significant corrugation of the graphene overlayer with consequent important modification of its electronic band structure and transport properties. In particular, we show that a small gap ( E G ∼ 0.16 eV) opens in the electronic band structure of the graphene/SiO 2 system, and the conical features around the Dirac points are lost. Correspondingly, at the graphene/SiO 2 interface, the diffuse π − π conjugation of the isolated graphene layer is modified by the appearance of near' sp 3 carbon atoms bound to the top oxygens of the SiO 2 . This fact also affects conductances and I – V characteristics which become different along different cell directions of the graphene overlayer. Our analysis suggests that the energy barrier between the van der Waals and the covalent minima could be overcome by applying a uniform pressure on the graphene overlayer due to the formation of chemical bonds which are important for the experimental integration of graphene on Si‐compatible technology.